SCENARIO-CASE APPROACH TO THE CONTROL OF HETEROGENEOUS ENSEMBLES OF DYNAMIC OBJECTS - Sherstjuk, V. G.; Sokol, I. V.; Tarasenko, E. N. (Science and Transport Progress, 2017)
Purpose. The article is devoted to developing the method of intelligent coordination control of a complex heterogeneous ensemble of dynamic objects. Methodology. The method of solving this problem is based on the case-scenario approach presenting the activity of dynamic objects as templates that adapt to changing external conditions by using scenarios. The algorithm of satisfaction of critical time constraints was used to adapt scenarios. The proposed method can adequately reflect the experience and knowledge of control of a dynamic objects’ group using similar decision stereotypes to control in similar situations. The main elements of case decisions such as control actions, operations, scenarios, and plans were described. Findings. The hybrid control system was implemented. The lower level of the system was developed based on the hybrid system BRIZ, which combining the subsystem based on cases with the subsystem that implements the movement model and so is master, while case subsystem is slave. The middle and top levels of the system were developed as the event-based hybrid system MUSSON, which includes case-scenario subsystem, storage subsystem and subsystem that calculating spatial regions based on the model. Scripts and triggers for each class of events were described by scripting language SCDL. Originality. The three-tier coordination control system for ensembles of dynamic objects based on case-scenario approach was proposed for the first time. The lower level is dedicated to control of separate dynamic objects, the second level is aimed to coordination of objects that jointly move, and the upper level provide the mission of the whole ensemble of dynamic objects. Practical value. The proposed approach is insensitive to inaccuracies and incomplete observations. It can reduce the information overload in the situation analysis, as well as decision-making time, thus increasing the efficiency of coordination of ensembles of dynamic objects during their mission’s execution process. Important conditions for the implementation of scenario-case method are to ensure sufficient competence that allows to find appropriate case and choose an adequate set of scenarios in time, and to synchronize each dynamic object’s case base in time and content.